2015
DOI: 10.1111/petr.12588
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes and predictors in pediatric liver retransplantation

Abstract: Historically, 9-29% of pediatric liver transplant recipients have required retransplantation. Although outcomes have improved over the last decade, currently published patient and graft survival remain lower after retransplant than after primary transplant. Data from liver retransplantation recipients at our institution between 1991 and 2013 were retrospectively reviewed. Kaplan-Meier estimates were used to depict patient and graft survival. Predictors of survival were analyzed using a series of Cox proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…In our study, since 1992, in 4.4% of LTs an eRe‐LT was necessary. In 67% of the patients, vascular complications led to the need for eRe‐LT, whereas in the remaining 33% the cause was PNF, similar to reports in other pediatric series …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, since 1992, in 4.4% of LTs an eRe‐LT was necessary. In 67% of the patients, vascular complications led to the need for eRe‐LT, whereas in the remaining 33% the cause was PNF, similar to reports in other pediatric series …”
Section: Discussionsupporting
confidence: 85%
“…In 67% of the patients, vascular complications led to the need for eRe-LT, whereas in the remaining 33% the cause was PNF, similar to reports in other pediatric series. (6)(7)(8)(9)(10)13,(16)(17)(18) Although over time there has been a trend toward better survival in patients undergoing eRe-LT, results are still significantly worse than after a first transplantation. (1,5,7,16,17,19,20) Also, results in patients undergoing eRe-LT are consistently worse than in those who undergo late re-LT, and prognosis in the eRe-LT patients is also worse than in those with the other classical indication for urgent LT: acute liver failure.…”
Section: Original Article | 533mentioning
confidence: 99%
“…In a study about complications and mortality after liver transplantation, both univariate and multivariate analyses revealed a significant association between vascular complication and mortality of recipients [23]. As another result of the current study, like the other studies, we found that PTLD can increase the risk of death [24, 25]. And finally in contrast to our study, factors like the recipient's age, comorbidity disease, previous abdominal surgery, and MELD were reported as death risk factors after transplantation [2, 14, 26].…”
Section: Discussionsupporting
confidence: 81%
“…The condition worsens with time in a large proportion of the cases and may lead to life‐threatening conditions and the need for surgery (including re‐transplantation or a possible portosystemic shunt). This fact questions the current typical strategy (conservative management until unmanageable complications arise) given that late surgery/transplantation in these patients carry a known high risk of suboptimal outcomes …”
Section: Discussionmentioning
confidence: 99%